Flypaper Effect of Regional Expenditure and It's Impact to Regional Inequality in Indonesia - Fitri Amalia (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
The primary objective of decentralization is expected to narrow down the regional gap among regions in Indonesia, which is considered as the result of a centralized development. The objective of this research is to identify the flypaper effect of regional expenditures of regency and city governments in Indonesia from 2008 until 2013. Another aim of this study is to provide an empirical evidence that the influence of regional expenditures of regencies and cities in Indonesia from 2009 until 2013 over the regional gap in Eastern and Western provinces of Indonesia. As such, it is necessary to use multiple regression analysis to examine the data. The findings of this study explicate that own-source revenue and general allocation fund significantly affect regional expenditures and a regional gap in the Eastern and Western provinces of Indonesia. Thus, it can be concluded that the dependency level of the regions upon a number of funds transferred from central government is still relatively high. In other words, the flypaper effect occurs in those regions.DOI: 10.15408/sjie.v6i1.3293